Cognitive biases and moral characteristics of healthcare workers and their treatment approach for persons with advanced dementia in acute care settings - Erel, Meira; Marcus, Esther-Lee; DeKeyser Ganz, Freda (Frontiers in Medicine, 2023)
Introduction: Palliative care (PC) delivery for persons with advanced dementia (AD) remains low, particularly in acute-care settings. Studies have shown that cognitive biases and moral characteristics can influence patient care through their effect on the thinking patterns of healthcare workers (HCWs). This study aimed to determine whether cognitive biases, including representativeness, availability, and anchoring, are associated with treatment approaches, ranging from palliative to aggressive care in acute medical situations, for persons with AD. Methods: 315 HCWs participated in this study: 159 physicians and 156 nurses from medical and surgical wards in two hospitals. The following questionnaires were administered: a socio-demographic questionnaire; the Moral Sensitivity Questionnaire; the Professional Moral Courage Scale; a case scenario of a person with AD presenting with pneumonia, with six possible interventions ranging from PC to aggressive care (referring to life-prolonging interventions), each given a score from (-1) (palliative) to 3 (aggressive), the sum of which is the “Treatment Approach Score;” and 12 items assessing perceptions regarding PC for dementia. Those items, the moral scores, and professional orientation (medical/surgical) were classified into the three cognitive biases. Results: The following aspects of cognitive biases were associated with the Treatment Approach Score: representativeness – agreement with the definition of dementia as a terminal disease and appropriateness of PC for dementia; availability – perceived organizational support for PC decisions, apprehension regarding response to PC decisions by seniors or family, and apprehension regarding a lawsuit following PC; and anchoring – perceived PC appropriateness by colleagues, comfort with end-of-life conversations, guilt feelings following the death of a patient, stress, and avoidance accompanying care. No association was found between moral characteristics and the treatment approach. In a multivariate analysis, the predictors of the care approach were: guilt feelings about the death of a patient, apprehension regarding senior-level response, and PC appropriateness for dementia. Conclusion: Cognitive biases were associated with the care decisions for persons with AD in acute medical conditions. These findings provide insight into the potential effects of cognitive biases on clinical decisions, which may explain the disparity between treatment guidelines and the deficiency in the implementation of palliation for this population.